2021
DOI: 10.1177/02654075211001435
|View full text |Cite
|
Sign up to set email alerts
|

Family, friendship, and strength among LGBTQ+ migrants in Cape Town, South Africa: A qualitative understanding

Abstract: The purpose of this qualitative study was to explore how migrants in South Africa identifying as lesbian, gay, bisexual, transgender, queer, or with other diverse sexual orientations or gender identities (LGBTQ+) describe and understand their pre-migration family experiences and how family and other social relationships facilitated strength during post-migration. We conducted six focus groups, consisting of both morning and afternoon sessions, which included a total of 30 LGBTQ+ migrants (ages 21–42). The foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Even when families of origin are accepting, LGBTQ+ individuals may still turn to their chosen family for social support, as often their family members may not be able to provide LGBTQ+-specific support in terms of guidance on coping with discrimination or seeking same-sex relationships (Williams et al, 2016). Chosen families and communities are also critical for supporting LGBTQ+ people who leave anti-LGBTQ+ environments and communities (Alessi et al, 2021). In addition, the support they offer ameliorates the association between family victimization and mental health outcomes (Parra et al, 2018).…”
Section: Social Support In and For Lgbtq+ Relationshipsmentioning
confidence: 99%
“…Even when families of origin are accepting, LGBTQ+ individuals may still turn to their chosen family for social support, as often their family members may not be able to provide LGBTQ+-specific support in terms of guidance on coping with discrimination or seeking same-sex relationships (Williams et al, 2016). Chosen families and communities are also critical for supporting LGBTQ+ people who leave anti-LGBTQ+ environments and communities (Alessi et al, 2021). In addition, the support they offer ameliorates the association between family victimization and mental health outcomes (Parra et al, 2018).…”
Section: Social Support In and For Lgbtq+ Relationshipsmentioning
confidence: 99%
“…One study demonstrated strong positive associations between minority stressors (loneliness and sexual orientation concealment), barriers to integration (lack of English language proficiency and insecure citizenship status) and psychological distress among LGBTQ+ migrants in the United States and Canada (Fox et al, 2020). Without these connections, LGBTQ+ migrants must find other ways to integrate; and evidence has shown they forge new relationships by relying on other LGBTQ+ migrants and community organizations, which can substitute, in part, for the emotional and practical support they may not receive from family and diaspora communities (Alessi et al, 2021; Kahn et al, 2018; Logie et al, 2016).…”
Section: Lesbian Gay Bisexual Transgender Queer Migrationmentioning
confidence: 99%
“…This study demonstrated the centrality of sexuality-specific support to the provision of beneficial emotional, informational, and instrumental support by groups outside the LGBTQ community, including families of origin, healthcare providers, and others including work colleagues and police. Most research has focused on Kenyan families' responses to learning that their child has a minority sexual orientation and has identified stigmatizing and rejecting behaviors including being kicked out of the family home, deprived of tuition payments and other previously provided economic support, and physical violence [6,39]. While this is not inconsistent with our research, our findings demonstrate variability in the response of Kenyan families; some families of origin are accepting of GBMSM family members or, even if not accepting of their sexual orientation, still provide love and support.…”
Section: Study Implicationsmentioning
confidence: 99%